PEMBERDAYAAN MASYARAKAT DALAM MENCIPTAKAN KESEJAHTERAAN KELUARGA MELALUI BUDIDAYA JAGUNG DI DESA SARIMATONDANG - Muhammad Yunus; Eka Pratiwi Septania Parapat (Politeknik Bisnis Indonesia, 2021)
This study aims to determine the influence of the government's role, the role of the private sector, and the role of NGOs on community empowerment through corn cultivation in Sarimatondang Village. In addition, this study also aims to find out how community empowerment can affect family welfare. This research is a type of causal associative research conducted with a quantitative approach. The population used in this study were corn farmers in Sarimatondang Village, Sidamanik District. Data collection techniques in this study used questionnaires, interviews and literature studies. While the method of data analysis was carried out using the PLS technique. The results in this study are expected to be input for the village community in developing the empowerment of corn cultivation in Sarimatondang Village, Sidamanik District, Simalungun Regency by knowing how the synergy of each role of the government, the private sector and NGOs is. he role of the government and the private sector is proven to have a positive and significant influence on community empowerment through corn cultivation. In addition, it is also proven that community empowerment has a positive influence on family welfare in Sarimatondang Village, Sidamanik District.